The ecological botany of the subantarctic islands of New Zealand - Cockayne, L. (Wellington, 1909)
Flora Oceanía N. Zelandia
Subantarctic Islands of New Zealand, Article X
Keywords: Flora; Antartida; Nueva Zelandia